Export market orientation from brazilian coffee - Brandão, Fernanda Scharnberg; Ceolin, Alessandra Carla; Gianezini, Miguelangelo; Ruviaro, Clandio Favarini; Dias, Eduardo Antunes; Barcellos, Júlio Otávio Jardim (Coffee Science - ISSN 1984-3909, 2012)
This paper aims to verify whether the Regional Orientation Index (ROI) can assist in decision making for export marketorientation for Brazilian coffee, to export the searching products from the major importers. The Decision Making Theory was adoptedand through the descriptive and quantitative method, the ROI is calculated in order to determine if Brazilian coffee exports are beingaddressed to the main importers. The data source of Brazilian green coffee used is the ALICEWEB base, linked to the Department ofCommerce (SECEX) of the Ministry of Industry and Trade (MDIC) for the period studied from 2000 to 2009 in US dollars (USD). Weobserved that coffee exports have been less directed towards countries like Canada, Netherlands, France, Italy, Belgium and Spain,with emphasis on decline of the ROI in Slovenia. The results also show that the Brazilian green coffee have been exported for Sweden,Finland, Japan, Germany, USA. The ROI shows increasing values for these regions, noting that over 40% of coffee imports arerepresented by Germany and USA, which are important markets for Brazil to follow when directing their exports. The originality ofthis study is to assist the decision makers through the ROI methodology for export market orientation for Brazilian coffee, accordingto the behavior and development of exports. This approach along with other economic indicators may indicate possibilities related tothe implementation of trade policies in order to redirect products to specific markets.